Targeted Metabolomics Analysis of Serum Amino Acids in T2DM Patients - Bao L; Wu B; Yang C; Xu X; Shi Z; Jiang D (Diabetes, Metabolic Syndrome and Obesity, 2024)
Li Bao,1,2 Bowen Wu,3 Chunjing Yang,1,2 Xiqiao Xu,1,2 Zhengyuan Shi,1,2 Dechun Jiang1,2 1Department of Pharmacy, Beijing Shijitan Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Beijing Key Laboratory of Bio-Characteristic Profiling for Evaluation of Rational Drug Use, Beijing, People’s Republic of China; 3Institute for TCM-X, MOE Key Laboratory of Bioinformatics, Bioinformatics Division, BNRIST, Department of Automation, Tsinghua University, Beijing, People’s Republic of ChinaCorrespondence: Zhengyuan Shi; Dechun Jiang, Department of Pharmacy, Beijing Shijitan Hospital, Capital Medical University, No. 10 Tieyi-Road, Haidian District, Beijing, 10038, People’s Republic of China, Tel +86-10-63926405 ; +86-10-63926723, Email shizhengyuan2980@bjsjth.cn; jdc@bjsjth.cnPurpose: Amino acids are the important metabolites in the body and play a crucial role in biological processes. The purpose of this study is to provide a profile of amino acids change in the serum of T2DM patients and identify potential biomarkers.Patients and Methods: In this study, we quantitatively determined the serum amino acid profiles of 30 T2DM patients and 30 healthy volunteers. T test and multivariate statistical analysis were used to identify candidate biomarkers with GraphPad Prism 9.5 software and MetaboAnalyst 5.0 on-line platform.Results: Thirty-four amino acids were quantified, and 19 amino acid levels differed significantly between T2DM and Healthy groups. Screened by the specific screening criteria (VIP> 1.0; P< 0.05; FC> 1.5, or FC< 0.67) in MetaboAnalyst 5.0 platform, 8 amino acids were identified as potential biomarkers. Pearson rank correlation test showed 14 differential amino acids were significantly correlated with T2DM-related physiological parameters.Conclusion: The results of this study provide theoretical basis for the subsequent development of dietary supplements for the prevention or treatment of T2DM and its complications.Keywords: diabetes mellitus type 2, T2DM, targeted metabolomics, amino acids, biomarker